EFFECTS OF BANDITRY ON RUMINANT ANIMAL PRODUCTION IN KATSINA STATE (FUDMA JOURNAL OF SCIENCES, 2021)
Ruminant animal production has recently come under a big threat due to the challenges of insecurity. This study was conducted to assess the effect of banditry on ruminant animal production in Katsina state. Using a two-stage sampling procedure,   60 ruminant animal farmers (keeping cattle, sheep and goats) in the state were selected for the study. In the first stage, three livestock markets from each of the state agricultural zones namely: Maiâ€™dua, Charanchi and Sheme markets were purposively selected based on the volume of ruminant animal sold there. The use of livestock markets was because of the difficulty of accessing the famers in their homes due to the prevalent security challenges in the study area. In the second stage, 60 questionnaires were randomly distributed to ruminant animal producers identified in the markets. However, only 44 were used due to incomplete information. The information gathered was analyzed using descriptive statistics. The study revealed that 66% of the respondent were within the age of 41-60 years, married (93%) and educated (57%). Similarly, majority of the respondents (64%) have large families. According to the study, the most prominent system of production used was Semi-intensive (29%) and forage was the major source of feed (70%). The study concluded that banditry has significantly reduced the ruminant production in the study area with untold negative effect on their standard of living and that government should improve security in the study area
Keywords: Ruminants, farming, banditry, production